Impact of magnetic fields on calculated AAPM TG-43 parameters for 192Ir and 60Co HDR brachytherapy sources: A Monte Carlo study. (May 2020) - Ranjbar, Sahar; Gholami, Somayeh; Longo, Francesco; Sharp, Ryan; Meigooni, Ali S.
Abstract: Purpose: The aim of this work is to investigate the influence of an external magnetic field (MF) on The American Association of Physicists in Medicine (AAPM) No. 43 Report (TG-43) parameters for 192 Ir and 60 Co high dose rate (HDR) brachytherapy sources using Monte Carlo (MC) simulation methods. Materials and methods: We used the Geant4 toolkit (version 10.1. p01) to simulate the geometry of 192 Ir and 60 Co brachytherapy sources. AAPM TG-43 parameters (the radial dose function, g(r), and the anisotropy function, F (r, θ)) of both 192 Ir and 60 Co sources were calculated in the presence of a magnetic field with strengths of 1.5T, 3T, and 7T in the X, Y, and Z directions in a voxelized water phantom. Results: For the 192 Ir source, the calculated values g(r) and F (r, θ) remained nearly unaffected by the magnetic field for all investigated strengths. For the 60 Co source, the differences for the g(r) and F (r, θ) under the 1.5T, 3T, and 7T magnetic field strengths along the direction parallel with the MF were found to be an increase of up to 5%, 15%, and 33%, respectively. However, for the directions perpendicular with the magnetic field, there was a decrease of up to 3%, 6% and 15% under 1.5T, 3T and 7T strengths, respectively. Conclusion: Our results highlight the necessity of a Monte Carlo-based treatment planning system (TPS) if cobalt HDR treatments are performed under a magnetic field, especially for strengths greater than 1.5T. Highlights: For the 192 Ir source, the TG-43 parameters remained nearly unaffected by the magnetic field for all investigated strengths. For the 60 Co source, the TG-43 parameters can differ up to 33% under 7T magnetic field. The necessity of a Monte Carlo-based TPS was demonstrated if 60 Co HDR treatments are performed under a magnetic field.